Результати моделювання роботи колісного трактора з гідрооб'ємно-механічними трансмісіями, що працюють по схемі "диференціал на вході" - Кожушко, Андрій Павлович (Луцький національний технічний університет, 2015)
В роботі наведено зміну перепаду робочого тиску в гідрооб'ємній передачі, коефіцієнта корисної дії трансмісії та годинної витрати палива в процесі розгону колісного трактора з гідрооб’ємно-механічними трансмісіями, що працюють по схемі «диференціал на вході», при виконанні технологічної операції «оранка» та різних законах зміни: коефіцієнта, котрий характеризує положення органу керування подачею палива, параметрів регулювання гідромашин гідрооб’ємної передачі, сили тяги на гаку.

This paper describes the process of acceleration wheel tractor with hydrostatic mechanical transmissions working under the scheme "planetary gear input", the performance of technological operations "plowing". On the basis of recent studies were selected two schemes hydrostatic mechanical transmissions that during static analysis had the greatest coefficient useful action transmission. Also reviewed publications that describe the mathematical model of internal combustion engines, hydrostatic mechanical transmission, interaction with wheels supporting surface and determine the feasibility indicators wheeled tractors, including hourly fuel consumption of the internal combustion engine in the system software implementation using Matlab subsystem Simulink modeling of dynamic processes was composed only mathematical model. Simulated single mathematical model was able to vary with respect to time change laws: coefficient, which describes the position of the controls fuel delivery, parameters for controlling fluid of hydraulic transmission, traction on the hook. As a result of a comparative analysis of the maximum working pressure difference results in the transfer of hydraulic, the coefficient useful action of transmission and hourly fuel consumption internal combustion engine was concluded, the use of which is the law of change: the factor, which characterizes the position of the controls fuel delivery, regulation parameters of hydraulic fluid transmission, traction on the hook will increase of efficiency and cost-wheel tractor.
Simulation results of work wheel tractor with hydrostatic mechanical transmissions working on schemes for "planetary gear input"
Keywords: трактор колісний; розгін; трансмісія гідрооб'ємно-механічна; оранка; wheeled tractor; acceleration; hydrostatic mechanical transmission; plowing